Identification and critique of the citizenship notion informing the Itorero training scheme for high school leavers in post-genocide Rwanda - Nzahabwanayo, S.; Horsthemke, K.; Mathebula, T.P. (South African Journal of Higher Education, 2017)
There is a dearth of research on citizenship education in post-genocide countries. The present article investigates the citizenship concept informing Itorero, a non-formal citizenship education platform meant for High School Leavers (hereafter HSLs) in post-genocide Rwanda. To this end, the paper engages with classical notions of citizenship (civic republicanism, liberalism and communitarianism), and modern ones (cosmopolitanism and radical democracy) in a bid to identify the notion deemed preferable to competing notions. It is revealed that the Itorero training relies heavily on the civic republican/communitarian concepts of citizenship. The paper argues that while these concepts contain constructive elements, such as fostering courage, self-sacrifice, patriotism, connectedness, and common good concern, excessive pursuit of this citizenship model might not be helpful for post-genocide Rwanda. The civic republican/communitarian paradigm – as it is practiced in Itorerotraining – is likely to produce uncritical, docile, dependent, short-sighted and child-like citizens; it encourages fanaticism.